ANALISIS PENGARUH CSR DISCLOSURE TERHADAP FINANCIAL PERFORMANCE DENGAN FINANCIAL LEVERAGE DAN COMPANY SIZE SEBAGAI VARIABEL MODERATING - Hamdani Arifulsyah; Suci Nurulita (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: The aims of this study was to determine: (1) The effect of  CSR Disclosure to  the financial performance (2) The effect of CSR Disclosure to financial performance with financial leverage as moderating variable (3) The Effect of CSR Disclosure to  financial performance with company size as moderating variable. The sample was the plantation sector companies in year from 2012 to 2014 using the method purposive sampling. The method of analysis in this research is simple regression analysis and multiple regression analysis. The results showed that (1) the disclosure  has  significant effect on financial performance. (2) financial leverage as moderating variables can affect relationships  CSR disclosure with  financial performanve. And (3) company size as moderating variables can affect the relationship CSR disclosure with financial performance. Keywords: ROA, CSR Disclosure, DER, Total assets